Biochemistry and laboratory diagnosis of obesity: Laboratory diagnosis of obesity - Milinković, Neda; Bogavac-Stanojević, Nataša; Vekić, Jelena; Jovičić, Snežana; Kotur-Stevuljević, Jelena (Archives of Pharmacy, 2024)
Until now, a lot of research has been carried out which significantly helped in understanding and solving the problem of obesity. Despite this, there has been an upward in obesity trend at the global level. The role of laboratory diagnostics in the field of obesity is of great importance to doctors for establishing a diagnosis and monitoring the effects of therapy. Determining biochemical parameters also contributes to practical usefulness in the prevention of this disease, and prevention of consequent complications. Routinely available biochemical analyses are usually used to diagnose and monitor the effects of obesity therapy. The initial association related to laboratory analyses refers to parameters of lipid status, but there are a variety of routine laboratory parameters that can help in understanding and monitoring obesity from different angles. Timely and adequate management of obesity is also of interest from an economic aspect. For this reason, the topic of this research is to summarize the latest aspects of the concept of obesity, specifically from the point of view of biochemistry and laboratory diagnostics. Taking into account the complexity of this disease, it is important to point out the future perspectives and challenges that inevitably arise before both laboratory professionals and healthcare providers in general.